The Effect of Exchange Rate Volatility, BI 7 DRR (Reverse), and Islamic Capital Market on Indonesia's Economic Growth with Inflation as an Intervening Variable - Raja Zainal Abidin Harahap; Ikhwanuddin Harahap; Rukiah (Universitas Muhammadiyah Surabaya, 2023)
This research is motivated by a phenomenon, namely Indonesia's economic growth which is quite significant, especially after being hit by the Covid-19 storm that occurred in 2020. In some literature and theories, it is stated that one of the things that can increase economic growth again is investment, be it through exchange rate volatility, BI 7 DRR (Reverse) policy and also the Islamic capital market, but in fact this investment does not have a significant impact on economic growth. So, the purpose of this study is to find out how the actual influence between exchange rate volatility, BI 7 DRR (Reverse) policy and also the Islamic capital market on economic growth both directly and indirectly through inflation. The discussion of this research is related to macroeconomics and the factors that influence it, besides that researcher need to see how the trend of Indonesia's gross domestic product from year to year.Â So that the approach taken is theories related to GDP, inflation rates, changes in exchange rate volatility, BI 7 DRR (Reverse) and Islamic capital markets. This research is quantitative research. The sample of this study was 84 samples. The data collection instrument was carried out by looking at the Indonesian economic growth report published on the website www.bi.go.id. Data analysis uses classical assumption test, t test, F test, path analysis, and sobel test. Based on the results of the study, it is known that there is an influence of the BI 7 DRR (Reverse) variable on inflation (4.338> 1.663). There is an influence of Islamic capital market variables on Indonesia's economic growth (6.003 > 1.663). There is an influence of the intervening variable of inflation on Indonesia's economic growth (9.696 > 1.663). The effect of exchange rate volatility variables, BI 7 DRR (Reverse) and Islamic capital markets on the intervening variable (inflation) is 21 percent while 79 percent is influenced by other variables outside this study. The value of the influence between the variables of exchange rate volatility, BI 7 DRR (Reverse), Islamic capital markets and intervening variables (inflation) on Indonesia's economic growth is 72 percent while 28 percent is influenced by other variables outside this study.